Effects of Different Milk-Tube Guidance Settings and Teat-Cup Types on the Dynamics of Teat-End Vacuum and Vacuum Fluctuations During Machine Milking - Adnan Değirmencioğlu; Hülya Öz; Erdal Öz; Philipp Thiele; Susanna Demba; Sandra Rose; Ulrich Ströbel (Journal of Agricultural Sciences)
The objective of this study was to determine the effects of milk tube guidance setting and teat cup type on the dynamics of teat-end vacuum and vacuum fluctuations in quarter individual milking systems. In order to meet this objective, a series of wet tests was conducted in the laboratory. Different teat cups; AMS, BIO and RVS along with the milk tube guidance settings namely; direct tube, half-half tube and Y-piece tube system with varying tube inside diameters were tested at different water flow rates. The data obtained from the wet-test measurements were used to calculate the teat-end vacuum and vacuum fluctuation at the teat-end in b and d- phase. From the study conducted, it was found that the teat-end vacuum in BIO is always between the range of 32 and 42 kPa as recommended by DIN ISO 5707 (2010a) at any flow rate for all three types of connections. The teat-end vacuum for RVS was between 32-42 kPa range if the flow rate varies between 4 and 6 L min-1 for both, the direct and the half-half connection. The Y-piece connection meets DIN ISO 5707 (2010a) requirements once the flow rate changes between 2 and 6 L min-1. The findings about milk tube inside diameter indicated that the use of 14 or 16 mm milk tube diameter for BIO will provide better teat-end vacuum if the recommended value of 10 mm is used. On the other hand, the use of 16 mm milk tube diameter was found to be appropriate for AMS as recommended by the manufacturer. For the RVS, the appropriate milk tube diameter should be 14 mm when statistical differences in b and d-phase are examined from the point of teat-end vacuum and vacuum fluctuations.